Effect of Electrode and Electrolyte Thicknesses on All-Solid-State Battery Performance Analyzed With the Sand Equation - Devaux, Didier; Leduc, Hugo; Dumaz, Philippe; Lecuyer, Margaux; Deschamps, Marc; Bouchet, Renaud (Frontiers in Energy Research, 2020)
The energy conversion and storage are great challenges for our society. Despite the progress accomplished by the Lithium(Li)-ion technology based on flammable liquid electrolyte, their intrinsic instability is the strong safety issue for large scale applications. The use of solid polymer electrolytes (SPEs) is an adequate solution in terms of safety and energy density. To increase the energy density (resp. specific energy) of the batteries, the positive electrode thickness must be augmented. However, as for Li-ion liquid electrolyte, the cationic transference number of SPEs is low, typically below 0.2, which limits their power performance because of the formation of strong gradient of concentration throughout the battery. Thus, for a given battery system a compromise between the energy density and the power has to be found in a rapid manner. The goal of this study is to propose a simple efficient methodology to optimize the thickness of the SPE and the positive electrode based on charge transport parameters, which allows to determine the effective limiting Li+ diffusion coefficient. First, we rapidly establish the battery power performance thanks to a specific discharge protocol. Then, by using an approach based on the Sand equation a limiting current density is determined. A unique mother curve of the capacity as a function of the limiting current density is obtained whatever the electrode and electrolyte thicknesses. Finally, the effective limiting diffusion coefficient is estimated which in turn allows to design the best electrode depending on electrolyte thickness.